Knowledge, attitude and practice about radiation safety among the undergraduates in Eastern province dental college - M Nazargi Mahabob; Mahmoud Alabdulsalam; Abdulrahman Alabduladhem; Sulaiman Alfayz; Abdullah Alzuriq; Ali Mohammed Almomin (Journal of Pharmacy and Bioallied Sciences, 2021)
Background: Despite the fact that X-rays have a direct or indirect effect on tissues, imaging techniques have become an important part of modern dentistry, and dentists rely on them for diagnosis, treatment, and follow-up. This necessitates that dentists have adequate expertise and attitude in order to defend themselves and their patients. Aim: The present study was conducted to assess the knowledge, attitude, and practice of clinical side dental students and General Dental Practitioners (GDPs) regarding dental radiation protection safety protocol. Study Design: It is a prospective cross-section study among dental undergraduates and GDPs. Materials and Methods: One hundred and sixteen participants took part in this study and comprised 116 clinical side dental students and GDPs. Participants' data were gathered through a questionnaire that asked about their knowledge and practice of radiation biology, danger, and protection. Collected data subjected to statistical analysis using the SPSS 21. Pearson Chi-square test was done to evaluate the statistical significance. The P value fixed at ≤ 0.05 for significant. Results: From 116 participants, around 89.7%% of the participants believed that dental X-rays are harmful and 81% are having knowledge about annual radiation dose limit for a dentist, and overall, 56% of the participants were aware about the harmful effects of radiation exposure. Conclusion: There is a need to expand the curriculum to provide better exposure to radiation protection and its practice so that these students on graduation will be well-grounded with the principle governing dental radiography.